ANALISIS PENERAPAN PSAP NO. 07 TENTANG AKUNTANSI ASET TETAP PADA BALAI PENYANTUNAN LANJUT USIA â€œSENJA CERAHâ€ - Kumesan, Novita Melina; Kalangi, Lintje; Lambey, Robert (GOING CONCERN : JURNAL RISET AKUNTANSI, 2016)
Statement of Government Accounting Standards (PSAP) 07 is the standard for the accounting of fixed assets include the recognition, the determination of the carrying value, the accounting treatment of the revaluation and impairment of the carrying (carrying value) of fixed assets. Fixed assets have a very important role and should be managed well in order to produce reliable information in the financial statements. This study aims to determine the suitability of adoption of a PSAP 07 on fixed asset accounting in the Balai Penyantunan Lanjut Usia (BPLU) â€œSenja Cerahâ€. The data used is the statement of financial position, the card inventory items, journal transactions, and notes to the financial statements. The method used is descriptive analysis method. The results showed BPLU â€œSenja Cerahâ€ in the application of accounting of fixed assets, namely the classification, recognition, measurement / assessment, expenses after the acquisition, termination and release, as well as the disclosure is in accordance with the PSAP 07, but BPLU â€œSenja Cerahâ€ does not record depreciation of fixed assets owned so the treatment of depreciation of fixed assets is not in accordance with the PSAP 07. BPLU â€œSenja Cerahâ€ are expected to do so that the carrying value of depreciation of fixed assets truth. Keywords :PSAP 07, Fixed Assets